Oxide accumulation effects on wire + arc layer-by-layer additive manufacture process - Xu, Xiangfang; Ding, Jialuo; Ganguly, Supriyo; Diao, Chenglei; Williams, Stewart W. (Elsevier, 2017)
A maraging steel wall structure was built layer-by-layer to study oxide accumulation mechanisms and the influence of oxides on the subsequent deposition. An online arc welding camera was also applied to investigate the wetting and spreading behaviour of the deposition on different surface conditions. Two maraging steel walls were deposited under torch shielding only and torch plus tent shielding conditions respectively to study the effect of oxides on the mechanical properties. Upon deposition a mixture of Fe, Al and Ti oxides formed, floated to the weld pool surface and accumulated layer by layer, deteriorating the surface condition such that it was rough and porous, which adversely affected the stability of arc and the wetting and spreading process of the weld pool in subsequent layers. The accumulation of oxides added to the uncertainty of the layer dimension and worsened the surface finish to reduce the structural integrity. Despite that the majority of the oxides floated to the weld pool surface, oxides (up to a few hundred nanometers in diameter) were found to be dispersed in the additively manufactured structure and might be one of the strengthening sources resulting in a 11% increase in UTS and a 19% decrease in elongation compared to the structure built in the torch plus tent shielding condition.
Keywords: Wire + arc additive manufacture; Oxides accumulation; Wetting and spreading; Maraging steel